2023
DOI: 10.1007/s10802-023-01034-3
|View full text |Cite
|
Sign up to set email alerts
|

Co-Developmental Trajectories of Parental Psychological Distress and Child Internalizing and Externalizing Problems in Childhood and Adolescence: Associations with Self-Harm and Suicide Attempts

Abstract: Growing evidence has suggested that parental mental illness and child internalizing and externalizing problems tend to co-occur and engender risk for adverse child outcomes; however, there is considerable heterogeneity in their joint developmental trajectories. This study aimed to evaluate the joint developmental trajectories of maternal and paternal psychological distress and child internalizing and externalizing problems from early childhood to middle adolescence. Given that suicide and self-harm are major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(60 reference statements)
2
3
0
Order By: Relevance
“…Results showed that children in the high-HI + NC + PA trajectory class suffered the highest number of negative outcomes. These findings are in line with other studies examining later social maladjustment in youth with co-occurring externalizing and internalizing problems (Dugré et al, 2020; Fanti & Henrich, 2010; Murray et al, 2022; Vergunst et al, 2023; Winsper et al, 2020; Zhu et al, 2023). As those studies’ trajectories spanned from preschool to adolescence (i.e., age 2–16), children following high EBs trajectories with co-occurring internalizing problems already during the preschool years are likely at risk of similar problems.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Results showed that children in the high-HI + NC + PA trajectory class suffered the highest number of negative outcomes. These findings are in line with other studies examining later social maladjustment in youth with co-occurring externalizing and internalizing problems (Dugré et al, 2020; Fanti & Henrich, 2010; Murray et al, 2022; Vergunst et al, 2023; Winsper et al, 2020; Zhu et al, 2023). As those studies’ trajectories spanned from preschool to adolescence (i.e., age 2–16), children following high EBs trajectories with co-occurring internalizing problems already during the preschool years are likely at risk of similar problems.…”
Section: Discussionsupporting
confidence: 92%
“…The aim of the present study was to investigate whether distinct developmental EBs patterns are concurrently and possibly differentially associated with three facets of internalizing problems (i.e., general anxiety, separation anxiety, and depressive symptoms) throughout the preschool years in a population birth cohort. As expected, findings concord with prior reports that internalizing problems are positively associated with EBs (Dugré et al, 2020; Fanti & Henrich, 2010; Girard, 2021; Goulter et al, 2021; Morales et al, 2024; Murray et al, 2022; Speyer et al, 2022; Vergunst et al, 2023; Winsper et al, 2020; Zhu et al, 2023). Specifically, higher levels of general anxiety, separation anxiety, and depressive symptoms from the early to late preschool years were observed in children following high EBs trajectories, when compared to their peers who followed a low or moderate trajectory for all EBs across the preschool years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In order to characterize the normative temperamental and clinical features of the sample, parents/guardians of the participants completed two measures: the Child Behavior Questionnaire -Short Form (CBQ; Putnam & Rothbart, 2006) and the Multidimensional Assessment Profiles (MAPS; Krogh-Jespersen et al, 2022;Zhang et al, 2023). The anger/ frustration subscale of the CBQ is six items and was used as a measure of irritable temperament, consistent with previous studies (Fishburn et al, 2019;Karim & Perlman, 2017;Silver et al, 2023).…”
Section: Sample Characteristics and Questionnaire Measuresmentioning
confidence: 97%